2015
DOI: 10.18267/j.pep.529
|View full text |Cite
|
Sign up to set email alerts
|

To Lend or to Borrow on the Interbank Market: What Matters for Commercial Banks in the Visegrad Countries

Abstract: Abstract:The aim of this paper is to fi nd out determinants which aff ect the commercial banks´ decision to lend on the interbank market in the Visegrad countries. The data cover the period from 2000 to 2011. The net interbank position of individual banking sectors signifi cantly diff ers. Results of the probit model showed that banks´ decision to lend in interbank market is determined both by bank-specifi c and macroeconomic factors. Bank liquidity, capital adequacy and quality of the loan portfolio are impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Again, in some countries, the effect of the interest rate on bank liquidity is positive (e.g., Agénor et al, 2000;Bunda & Desquilbet, 2008;Dinger, 2009;Fielding & Shortland, 2005;Lucchetta, 2007;Moore, 2010;Munteanu, 2012;Vodová, 2013;, while in other countries or periods, the interest rate adversely affects bank liquidity (see Aspachs et al, 2005;Bunda & Desquilbet, 2008;Grant, 2012;Lucchetta, 2007;Moore, 2010;Munteanu, 2012;Rauch et al, 2010;or Vodová, 2013 and. The same, e.g., mixed results, can also be observed for the interest margin -a negative impact in Aspachs et al (2005) or Grant (2012); while a positive link is reported by Vodová (2015). A positive relationship between interest rates and bank liquidity is connected with the problem of credit rationing, while a negative link indicates that if lending activity is more profi table, banks will hold a smaller buffer of liquid assets and prefer to provide loans.…”
Section: XXsupporting
confidence: 52%
“…Again, in some countries, the effect of the interest rate on bank liquidity is positive (e.g., Agénor et al, 2000;Bunda & Desquilbet, 2008;Dinger, 2009;Fielding & Shortland, 2005;Lucchetta, 2007;Moore, 2010;Munteanu, 2012;Vodová, 2013;, while in other countries or periods, the interest rate adversely affects bank liquidity (see Aspachs et al, 2005;Bunda & Desquilbet, 2008;Grant, 2012;Lucchetta, 2007;Moore, 2010;Munteanu, 2012;Rauch et al, 2010;or Vodová, 2013 and. The same, e.g., mixed results, can also be observed for the interest margin -a negative impact in Aspachs et al (2005) or Grant (2012); while a positive link is reported by Vodová (2015). A positive relationship between interest rates and bank liquidity is connected with the problem of credit rationing, while a negative link indicates that if lending activity is more profi table, banks will hold a smaller buffer of liquid assets and prefer to provide loans.…”
Section: XXsupporting
confidence: 52%
“…On the other hand, the study conducted by Vodová (2013a) on Visegrad countries found a positive link between liquidity and GDP growth (lagged by one year). She argued that businesses need time to accumulate profits and savings before they will reduce their proportion of external financing which would result in higher bank liquidity.…”
Section: Macroeconomic Factors 221 Gross Domestic Products (Gdp)mentioning
confidence: 91%